Arginina no processo de translocação bacteriana: permeabilidade intestinal, vias de ação e resposta imunológica na obstrução intestinal induzida em camundongos - Mirelle Lomar Viana (2010)
This work evaluated the effects of arginine on intestinal mucosa integrity, bacterial translocation (BT) and immunomodulation in mice undergoing intestinal obstruction (IO). The role of nitric oxide (ON) was studied using L-NAME, a nitric oxide synthase blocker. The mice were divided in four groups, treated for seven days: ARG group fed a chow with 2% of arginine; ARG+L-NAME group, the same diet and L-NAME, by gavage; and groups Sham and IO, fed a standard chow. To assess intestinal permeability, on the 8th day the animals were gavaged with radiolabeled diethylene triamine pentaacetic acid solution and after 90 min, they were anesthetized and the ileum ligated, except the Sham group. At 4, 8 and 18 hours, blood was collected for radioactivity determination. Ileum samples were collected for histological analyses. Another group of animals, treated for 7 days was gavaged with 108 CFU/mL of 99mTechnetium-E.coli. Afterwards, the mice underwent the same surgical procedure described above and BT was determined by the uptake of 99mTechnetium-E.coli in mesenteric lymph nodes, blood, liver, spleen and lungs, 18 h after the operation. Blood and intestinal fluid were removed for serum cytokines (INF- and IL-10) and intestinal sIgA analysis. Arginine reduced intestinal permeability, BT and preserved mucosal integrity in mice undergoing IO. Arginine also increased the levels of IL-10 and sIgA when compared with groups Sham and IO. NO blockage did not prevent bacterial translocation, but preserved gut integrity. The levels of cytokines and sIgA were similar in the groups Sham and ARG+L-NAME. The current results suggest arginine protection against bacterial translocation through preservation of the intestinal mucosa integrity. Besides that, arginine modulated the immunological response and enhanced IgA production. NO has an important role in BT prevention, by modulation of the immunological response. The results show that arginine impacts on BT via nitric oxide production which on the other hand modulates the immunological response.